A taxonomy and design considerations for Internet accounting. - Kouadio, Michel (Computer communication review.)
Economic principles are increasingly being suggested for addressing some complex issues related to distributed resource allocation for QoS (Quality of Service) enhancement. Many proposals have been put forth, including various strategies from Pricing Theory and market-based insights for security in the Internet. A central need of these endeavors lies in the design of efficient accounting architecture for collecting, storing, processing and communicating relevant technical information to parties involved in transactions. This paper proceeds to a systematic classification of the major characteristics of accounting models with the aim of highlighting important features to optimize for building effective architectures.